Ethnic Categorization of Nigerian Banks: Causes, Effects and Moderating Conditions - Meksley Nwagboh (Journal of Marketing Development and Competitiveness, 2022)
Guided by the inter-organizational crisis between Guaranty Trust Bank and Innoson Group Limited in December 2017, this paper sought to examine how banks in Nigeria are categorized into ethnic groups and the factors influencing such categorizations. Social Identity Theory was used to explain group categorization. With the aid of a mixed-method research design, data was collated in three distinct phases from 795 participants. Findings revealed a high percentage of the study sample affirming the ethnic categorization of Nigerian banks into ethnic groups. Specifically, Fidelity Bank, Zenith Bank, and United Bank for Africa (UBA) were among the banks perceived by most participants as Igbo banks. In contrast, First Bank, Guaranty Trust Bank (GTBank), WEMA Bank, Union Bank, Ecobank, First City Monument Bank (FCMB) were perceived as Yoruba banks. Unity Bank cum Jaiz Bank is mentioned frequently in participants’ citations of Hausa banks.